TRADE AND GROWTH: NEW EMPIRICAL EVIDENCE FROM HONG KONG - Katircioglu, Salih Turan; Fethi, Sami; Aga, Mehmet (Wroclaw Univ Economics, 2010)
This study employs the bounds test for the level relationship and conditional Granger causality tests to test the trade-led growth hypothesis for Hong Kong. Results confirm the existence of long term relationship between real income and international trade volume in this country. International trade volume as proxied by exports of goods and services plus imports of goods and services has inelastic but statistically significant coefficient for real income both in the long and short terms. Results reveal that real income of Hong Kong converges to its long term level by 16.1% every year. A final finding of the present study is that conditional Granger causality tests suggest undirectional causation that runs from international trade volume to real income; thus, the trade-led growth hypothesis is confirmed in the case of Hong Kong according to the results of the present study.
Keywords: Trade; real income; bounds test; causality; Hong Kong